Guanidine aptamers are present in vertebrate RNAs associated with calcium signaling and neuromuscular function - Kumari Kavita; Aya Narunsky; Jessica J. Mohsen; Isha Mahadeshwar; Michael G. Mohsen; Yu-Shin Chang; Ronald R. Breaker (Nature Communications)
Abstract Guanidine is a protein denaturant that is a widely used constituent in explosives, plastics, and resins. Its effects on muscle contraction were initially reported in 1876, which eventually led to the use of guanidine as a treatment for certain ataxia symptoms such as those caused by Lambert-Eaton disease. However, its mechanisms of therapeutic action remained unknown. Guanidine was recently found to be a widespread natural metabolite through the discovery of four bacterial riboswitch classes that selectively recognize this compound. Here, we report the discovery and biochemical validation of vertebrate members of guanidine-I and -II riboswitch aptamer classes that are associated with numerous genes relevant to neuromuscular function, mostly involved in Ca2+ transport or signaling. These findings suggest that guanidine is a widely used signaling molecule that serves as an additional layer of regulation of genes relevant to neuromuscular disorders.